1983
DOI: 10.1099/00221287-129-10-3243
|View full text |Cite
|
Sign up to set email alerts
|

Fructosyltransferase Activity of a Glucan-binding Protein from Streptococcus mutans

Abstract: Streptococcus mutans serotype c produces several extracellular proteins which bind to affinity columns of immobilized glucans. The proteins are three distinct glucosyltransferases and another glucan-binding protein (molecular weight 74000) which is now shown to be a fructosyltransferase. This enzyme is antigenically distinct and genetically independent of two other fructosyltransferases produced by the same organism. A mutant is described which lacks the glucan binding fructosyltransferase and has defective ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
1
36
0
1
Order By: Relevance
“…Cariogenic streptococci produce several glucan-binding proteins, including GTF, fructosyltransferase (FTF), and non-enzymatic lectin-like proteins (McCabe and Hamelik, 1978;Russell, 1979;Russell et al, 1983). Results from the present study indicate that a significant amount of glucans synthesized by GTF adsorbed to saliva-coated surfaces remain attached to the mineral surface (Table 3).…”
Section: Discussionmentioning
confidence: 53%
“…Cariogenic streptococci produce several glucan-binding proteins, including GTF, fructosyltransferase (FTF), and non-enzymatic lectin-like proteins (McCabe and Hamelik, 1978;Russell, 1979;Russell et al, 1983). Results from the present study indicate that a significant amount of glucans synthesized by GTF adsorbed to saliva-coated surfaces remain attached to the mineral surface (Table 3).…”
Section: Discussionmentioning
confidence: 53%
“…have molecular masses of more than 100 kDa, the average bacterial FTFs molecular size. In 1983, Russell et al reported a glucan binding protein with FTF activity in S. mutans, but no explanation could be given for this property (29), so it is possible that the same recombination had taken place in S. mutans.…”
Section: Resultsmentioning
confidence: 99%
“…mutans tends to break down to yield multiple bands in the mol. wt range 50000-70000 (Russell et al, 1983a) and the GBP in E. coli lysates (Fig. lb) appears also to yield such minor bands.…”
Section: R E S U L T Smentioning
confidence: 99%
“…mutans supports our previous evidence for the apparent identity of GBP to one of the forms of FTF of S . mutans (Russell et al, 1983a).…”
Section: R E S U L T Smentioning
confidence: 99%